ANALISA KEGAGALAN PIN CONNECTION PADA RANGKAIAN PIPA PENGEBORAN SUMUR MINYAK BUMI - Haryo Mukarnadi Kuswandiyanto; Muhammad Sanusi; Bambang Teguh Prasetyo; Amin Suhadi (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2022)
ABSTRACT Oil and gas are natural resources. The oil drilling activity is one of the process series in oil exploration and production in order that the oil well always produces those natural resources constantly per days. Because of the reason in highly complexities, the success in oil drilling and exploration are also base on the quality of the equipments. This thesis has evaluated about pin connection. This is one of a part equipment that has been used in drill string series. The documentation of SOP, FAT and design specification are plays important role for the completeness of data histories. The material of pin connection is consists from some chemical substances. So the chemical composition in this pin connection have very important role to determine the mechanical properties of this part. These two combinations are give effect to its reliabilities performance. Keywords: SOP, FAT, Design, Chemical Composition, Mechanical Properties, Performance